2017
DOI: 10.1016/j.chemosphere.2017.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the oxidative and neurotoxic effects of glyphosate pesticide on the larvae of Rhamdia quelen fish

Abstract: The aim of this work was to investigate the effects of glyphosate on the antioxidant system, as well as the neurotoxic effects on the larvae of Rhamdia quelen. A completely randomized design was implemented with the eggs of silver catfish distributed in 48 containers with 300 mL of water, which were subdivided randomly into two groups: control and treated with 6.5 mg L of glyphosate. These groups were evaluated at four time points (12 h, 24 h, 48 h, and 72 h), each with six replications. The survival rate of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…AChE activity was used as a biomarker upon the exposure to pyrethroids, 23 and Toumi et al 7 suggested its high susceptibility in Daphnia magana after deltamethrin exposure. AChE inhibition also indicates the neurotoxic effect of substances to aquatic organisms 49,50 . In this test, AChE activity in muscles of P. clarkii decreased significantly in dose‐ and time‐dependent responses when exposed to 14 and 28 ng/L of deltamethrin.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…AChE activity was used as a biomarker upon the exposure to pyrethroids, 23 and Toumi et al 7 suggested its high susceptibility in Daphnia magana after deltamethrin exposure. AChE inhibition also indicates the neurotoxic effect of substances to aquatic organisms 49,50 . In this test, AChE activity in muscles of P. clarkii decreased significantly in dose‐ and time‐dependent responses when exposed to 14 and 28 ng/L of deltamethrin.…”
Section: Discussionmentioning
confidence: 92%
“…AChE inhibition also indicates the neurotoxic effect of substances to aquatic organisms. 49,50 In this test, AChE activity in muscles of P. clarkii decreased significantly in dose-and time-dependent responses when exposed to abamectin exposure, and DNA damage induced by ROS overproduction in cells was verified to be the main reason. 53 In addition, our previous study demonstrated that immunological function impairment in Eriocheir sinensis was related to oxidative stress under pesticide abamectin exposure.…”
Section: Suggested Its High Susceptibility Inmentioning
confidence: 83%
“…Anthropogenic activities such as changes in the natural courses of rivers, pollution, deforestation, introduction of alien species and overfishing are deleterious to natural fish populations (Sobjak et al, 2017). Moreover, environmental disasters, such as occurred in the Brazilian cities of Mariana (2015) and Brumadinho (2019), leads to almost instantaneous death of hundreds of thousands of fish species and other life forms, strongly affecting the natural fish stocks and, consequently, the regional socioeconomic activities (Carvalho et al, 2017;Santos et al, 2018;Lopes et al, 2019;Pereira et al, 2019;Rudorff et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This residue was not previously considered to pose any risks to human health ( 4 ). However, recently, glyphosate has been demonstrated to induce embryo-toxic and neurotoxic effects in in vitro and in vivo studies ( 5 , 6 ). The teratogenic effect of glyphosate on early morphogenesis in embryos raises concerns regarding the clinical phenomenon including, birth defects and behavior disorders, seen in children exposed to glyphosate in the countryside ( 2 , 7 ).…”
Section: Introductionmentioning
confidence: 99%